MEDIA PEMBELAJARAN BAHASA MELALUI MEMBACA UJARAN BAGI PENYANDANG TUNARUNGU BERBASIS ANDROID - Azmi, Muhammad; M. Hafizulloh (Badan Penelitian dan Pengabdian Masyarakat (BP2M) STMIK Syaikh Zainuddin NW Anjani, 2023)
The communication system for the deaf is non-verbal (non-verbal) communication using signs, either hand movements or body signals and facial expressions. Deafness can be defined as a condition of hearing loss. Deaf children are children who experience hearing deficiencies and therefore require special services. Deaf children have difficulty observing sounds through their hearing, therefore they have to perceive sounds or sounds or someone's expressions through their sight. In this research the author examines and analyzes the problem of Android-based language learning media through speech reading for deaf people. The purpose of writing is as a tool or alternative medium to be able to learn how to read your opponent's lip movements in the communication process. This application uses the research and development (R&D) method and in designing this learning media application, it uses the ADDIE Model (Analysis, Design, Development, Implementation, and Evaluation). The result of this research is an Android-based language learning media application through speech reading for deaf people that has been created to help the learning process, especially between teachers and deaf students in learning at SLB Muhamadiyah Kelayu.